ERP indices for response inhibition are related to anxiety-related personality traits - Sehlmeyer, C.; Konrad, C.; Zwitserlood, P.; Arolt, V.; Falkenstein, M.; Beste, C. (Neuropsychologia, 2010)
Anxiety is often associated with impaired cognitive control and avoidance behaviour. The aim of this study was to investigate the effect of anxiety-related personality traits, such as anxiety sensitivity and trait anxiety, on event-related potentials of response inhibition in a standard Go/Nogo-paradigm. We focused on the Nogo-N2 and Nogo-P3 components, which probably represent different sub-processes of response inhibition. The Nogo-N2 was mainly influenced by trait anxiety, while it was slightly affected by anxiety sensitivity. In contrast, the Nogo-P3 was significantly associated with anxiety sensitivity, but was less affected by trait anxiety. Thus, anxious subjects seem to maintain a higher level of cognitive control to prepare and to monitor the outcome of their actions, which is differentially reflected in Nogo-N2 and Nogo-P3 potentials. Our results show that anxiety-related personality traits modulate electrophysiological responses related to cognitive control processes and should be taken into consideration in studies investigating response inhibition.